2015
DOI: 10.1152/ajplung.00236.2015
|View full text |Cite
|
Sign up to set email alerts
|

An oxidative DNA “damage” and repair mechanism localized in the VEGF promoter is important for hypoxia-induced VEGF mRNA expression

Abstract: In hypoxia, mitochondria-generated reactive oxygen species not only stimulate accumulation of the transcriptional regulator of hypoxic gene expression, hypoxia inducible factor-1 (Hif-1), but also cause oxidative base modifications in hypoxic response elements (HREs) of hypoxia-inducible genes. When the hypoxia-induced base modifications are suppressed, Hif-1 fails to associate with the HRE of the VEGF promoter, and VEGF mRNA accumulation is blunted. The mechanism linking base modifications to transcription is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
181
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(191 citation statements)
references
References 37 publications
9
181
0
1
Order By: Relevance
“…Hif1α, STAT1, NF-κB and MYC) in conjunction with OGG1 protein and, in turn, regulates the expression of important genes involved in cancer development, such as VEGF [40], SIRT-1 [41] and inflammatory genes such as TNF-α and CXCL2 [42]. Interestingly, this last role of OGG1 on inflammatory genes may explain the reduced inflammatory response in Ogg1 −/− mice [43].…”
Section: Unusual Involvement Of Ber Enzymes In the Regulation Of Genementioning
confidence: 99%
“…Hif1α, STAT1, NF-κB and MYC) in conjunction with OGG1 protein and, in turn, regulates the expression of important genes involved in cancer development, such as VEGF [40], SIRT-1 [41] and inflammatory genes such as TNF-α and CXCL2 [42]. Interestingly, this last role of OGG1 on inflammatory genes may explain the reduced inflammatory response in Ogg1 −/− mice [43].…”
Section: Unusual Involvement Of Ber Enzymes In the Regulation Of Genementioning
confidence: 99%
“…Most oxidative DNA damage is efficiently processed by DNA repair pathways, primarily base excision repair (BER), the molecular details of which are generally well understood (2). However, an emerging area of research posits that certain oxidative DNA lesions and their associated repair complexes are intermediates in a signaling transduction cascade that uses ROS as secondary messengers to ultimately effect transcriptional regulation (3)(4)(5)(6)(7). In PNAS, Fleming et al (8) reinforce these notions by describing a compelling mechanism by which 8-oxoguanine (OG), a canonical oxidative DNA damage product, when occurring in guanine-rich, G-quadruplex-forming promoter sequences, directly up-regulates transcription of the downstream gene.…”
mentioning
confidence: 99%
“…In the hypoxia field, it has been increasingly appreciated that the expression of hypoxia-inducible genes [e.g., vascular endothelial growth factor (VEGF)] depends, in part, on a controlled oxidative DNA damage and repair cycle (3,6). More intriguingly, even in normoxic conditions, the expression of estrogen-or androgenresponsive genes also requires DNA oxidation and repair (10,11).…”
mentioning
confidence: 99%
“…This provides a precedent that controlled DNA damage and repair can regulate active transcription. Other studies have also shown that site specific DNA damage can activate gene transcription (Ba et al 2014;Fleming, Ding, and Burrows 2017;Pan et al 2016;Pastukh et al 2015), though the mechanism through which damage occurs to specific points in the genome remains relatively unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…The resultant DNA lesion recruits OGG1 and topoisomerase IIb (TOPIIb) causing the conformational change to DNA required for gene activation (Perillo et al 2008). Likewise, oxidative damage to the vascular endothelial growth factor (VEGF) promoter enhances binding of hypoxiainducible factor 1a (HIF1a) with the subsequent assembly of BER components activating gene expression Ruchko 2009, 2010;Pastukh et al 2015). A similar process occurs in the promoters of tumor necrosis factor a (TNF-a) (Pan et al 2016) and sirtuin 1 (SIRT1) (Antoniali et al 2014).…”
Section: Journal Of Biological Chemistry 5457mentioning
confidence: 99%